1992
DOI: 10.1139/b92-138
|View full text |Cite
|
Sign up to set email alerts
|

Identification of physiological ecotypes in Hordeum jubatum based on responses to salinity stress

Abstract: Variability in salt tolerance of three populations of Hordeum jubatum was determined by analysis of growth parameters and ion relations of plants stressed with Na and Mg salts in solution culture experiments. Two populations from saline meadow habitats (Elstow and Floral) and one from a nonsaline site (University) were salinized with Na2SO4 and MgSO4 at Na:Mg molar ratios of 1:1 and 10:1. Elstow and Floral were more salt tolerant than University. University was more sensitive to the high Mg salt stress (Na:Mg,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

1994
1994
2024
2024

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 31 publications
0
7
0
Order By: Relevance
“…This search for local adaptation was prompted by the discovery of variation among the populations in salt tolerance under controlled conditions (Wang et al 1992). The analyses of survival, growth and fecundity among populations of H. jubatum in the present study showed that they were determined by transplant site factors (i.e.…”
Section: Discussionmentioning
confidence: 60%
See 4 more Smart Citations
“…This search for local adaptation was prompted by the discovery of variation among the populations in salt tolerance under controlled conditions (Wang et al 1992). The analyses of survival, growth and fecundity among populations of H. jubatum in the present study showed that they were determined by transplant site factors (i.e.…”
Section: Discussionmentioning
confidence: 60%
“…Percent survival of the UNI population at the FLO site was, however, significantly lower than that of the other two populations, which may be related to the higher Mg concentration in the soil of this site. Sensitivity of the seedlings from the UNI population to a high Mg salt treatment was shown in a hydroponic experiment (Wang et al 1992).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations